Samuel Hazard, Pennsylvania Archives. Selected And Arranged From Original Documents In The Office Of The Secretary Of The Commonwealth, Conformably To Acts Of The General Assembly, February 15, 1851, & March 1, 1852, at 160, As to the Act for the better Govemnt[sic] of the City iof Phila. (1852) - (:unkn) unknown (My University, 1713)
§This Act inflicts 5s penalty on persons riding a gallop and 10s for persons trotting, with Drays or their Teams in the streets, and 5th for suffering a Dog or a Bitch going at large; or firing a Gun without license
Keywords: DISCHARGE